2021
DOI: 10.3390/agronomy11101951
|View full text |Cite
|
Sign up to set email alerts
|

Design and Evaluation of a Crowdsourcing Precision Agriculture Mobile Application for Lambsquarters, Mission LQ

Abstract: Precision agriculture is highly dependent on the collection of high quality ground truth data to validate the algorithms used in prescription maps. However, the process of collecting ground truth data is labor-intensive and costly. One solution to increasing the collection of ground truth data is by recruiting citizen scientists through a crowdsourcing platform. In this study, a crowdsourcing platform application was built using a human-centered design process. The primary goals were to gauge users’ perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Primary and secondary economy (n = 14). Is such a domain focusing mainly on different aspects of agricultural, such as food security (Hampf et al 2021), as well as understanding how to use new technologies to further sustainable agriculture (Laso Bayas et al 2020;Posadas et al 2021;Thompson et al 2019). Other subdomains of economy are fishery management (Jeffers et al 2019;Silva et al 2022) and resource management (Bernedo Del Carpio et al 2021;Maynard et al 2020;Ogbe and Lujala, 2021).…”
Section: Results and Interpretationmentioning
confidence: 99%
“…Primary and secondary economy (n = 14). Is such a domain focusing mainly on different aspects of agricultural, such as food security (Hampf et al 2021), as well as understanding how to use new technologies to further sustainable agriculture (Laso Bayas et al 2020;Posadas et al 2021;Thompson et al 2019). Other subdomains of economy are fishery management (Jeffers et al 2019;Silva et al 2022) and resource management (Bernedo Del Carpio et al 2021;Maynard et al 2020;Ogbe and Lujala, 2021).…”
Section: Results and Interpretationmentioning
confidence: 99%
“…Although, one of the underserved research domains of HCI is agriculture [10]; however, a few researchers have investigated the importance of the role of HCI in the development of digital agriculture systems. Parker and Sinclair in [11] have reported that the adoption of a technology-centered approach is the main reason for the failure of the delivered device/tool/software that is not according to the needs of the farmers.…”
Section: Related Workmentioning
confidence: 99%
“…Mission LQ [10] A crowdsourcing Precision Agriculture platform (Android, iOS, Desktop versions) developed to teach people how to classify certain characteristics of Lambsquarters Agro App Mali [25] Android-based mobile application for farmers to get information about farming activities (Seed, pesticide, fertilizer availability) social-media mobile applications for realizing routine farming practices.…”
Section: Agfab Farmer-centered Agriculture Bowermentioning
confidence: 99%
“…In a study by Nozari et al (2021), the Internet of Everything technology was used as a crowdsourcing mechanism to promote company brand awareness and ensure sustainability and sustainable development. A mobile application was designed by Posadas et al (2021) to collect data for precision agriculture through the crowd, as a way of minimizing business costs while attaining an optimal solution. David (2020) highlights affordability as a determinant of farmer participation in crowdsourcing technologies like WhatsApp.…”
Section: Literature Review Css In Other Fieldsmentioning
confidence: 99%